2015
DOI: 10.1016/j.jval.2015.09.2483
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Literature Review of Health State Utility Values In Patients With Migraine

Abstract: GERAS is a prospective, non-interventional cohort study in AD patients and caregivers. The Zarit Burden Inventory (ZBI) and the EQ-5D were used to measure burden and HRQoL respectively. Spearman correlations were computed between EQ-5D, ZBI and T-IADL at baseline, 18-months and for change over 18-months. T-IADL and ZBI change scores were summarised by EQ-5D domain change category (better/stable/ worse). Results: 1495 caregivers were available at baseline [67 years (SD 12) and 64% female]. According to baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Previous studies have demonstrated reduced work productivity with greater headache frequencies [27,28]. In addition, the present study showed lower health utility scores, and health status ratings in the higher frequency subgroup (> 4 migraine headache days/month), which is consistent with previous studies [30].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have demonstrated reduced work productivity with greater headache frequencies [27,28]. In addition, the present study showed lower health utility scores, and health status ratings in the higher frequency subgroup (> 4 migraine headache days/month), which is consistent with previous studies [30].…”
Section: Discussionsupporting
confidence: 92%